Identification of Learning Independence Levels and Its Corelationship with Students Chemical Learning Outcomes at Covid-19 Era - Husnawati Husnawati; I Nyoman Loka; Baiq Fara Dwirani Sofia; Yunita Arian Sani Anwar (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
The purpose of this research was to determine the level of independence learning, chemical learning outcomes and the correlation between independence learning and chemical learning outcomes during the Covid-19 period in class XI MIPA SMAN 6 Mataram in 2020/2021. This type of research is called correlational research. The population used was all students from class XI MIPA SMAN 6 Mataram in 2020/2021, which consisted of 4 classes totaling 126 students and the sample used was 56 students using the Slovin formula. The sampling technique is proportional random sampling. Data in the form of the level of independence learning were collected using a questionnaire distribution technique, while the learning outcomes data were collected using a documentation technique from the value of chemistry test result. The data analysis technique used is non-parametric statistics using contingency correlation coefficient test. The results showed that the level of independence learning and chemical learning outcomes were categorized as moderate. The results also show a contingency correlation coefficient (C) which is 0.612 and compared to a rtable of 0.266 which shows there is a positive and significant relationship between independence learning and chemical learning outcomes during the Covid-19 period in class XI MIPA SMAN 6 Mataram Years 2020/2021